Basic Sciences in Anesthesia - Farag, Ehab; Argalious, Maged; Farag, Ehab.; Sharma, Deepak; Tetzlaff, John E. (Switzerland AG Springer, 2018)
This textbook presents the most recent evidenced-based knowledge in basic sciences in anesthesia. It covers topics from the syllabus of the American Board of Anesthesiology (ABA) basic science exam, including anatomy, pharmacology, physiology, physics in anesthesia, and more. In each chapter, key points summarize the content, followed by a pertinent and concise discussion of the topic, ending with multiple choice questions with answers and suggested further reading. Basic Sciences in Anesthesia is aimed at residents taking the ABA basic science of anesthesia examination, and any other anesthesiologist or trainee with an interest in the topic.
Section 1: Applied Anatomy -- Peripheral Nerve Block Anesthesia -- Central Neuraxial Anatomy and Anesthetic Application (Central Neuraxial Blockade) -- Anatomy of the Brain and the Spinal Cord -- Anatomy of the Airway/Airway Management -- Section 2: Pharmacology -- Pharmacology - General Concepts -- Pharmacology of Non-Opioid Intravenous Anesthetics -- Pharmacology of Opioids -- Clinical Pharmacology of Drugs Acting at the Neuromuscular Junction -- Pharmacology of Local and Neuraxial Anesthetics -- Pharmacology of Inhaled Anesthetics -- Cardiovascular Anatomy and Pharmacology -- Respiratory Pharmacology -- Renal Pharmacology -- Pharmacology of Anticoagulants, Antithrombotics, and Antiplatelet Drugs -- Perioperative Intravenous Fluid Therapy -- Section 3: Physiology -- Central and Peripheral Nervous Systems -- Cardiovascular Physiology -- Respiratory System Physiology -- Physiology of the Autonomic Nervous System -- Physiology of Temperature Control -- Gastrointestinal/Hepatic Physiology -- Renal Physiology -- Physiology of the Endocrine System and Metabolic Complications in Anesthesia -- Section 4: Anesthetic Management Topics -- Preoperative Evaluation of Patients Undergoing Non-Cardiac Surgery -- Premedication -- Monitored Anesthesia Care -- Blood Products Transfusion -- Complications in Anesthesia -- The Postoperative Period -- Perioperative Pain Management -- Special Problems in Anesthesiology -- Section 5: Physics in Anesthesia -- The Anesthesia Machine -- Physical Measurements in Anesthesia -- Breathing Systems -- Physics of Instrumentation -- Electrical Safety in the Operating Room -- Mechanical Ventilation -- Statistics Made Simple: Introduction to Biostatistics and Research Design for the Anesthesiologist.
Keywords: Anesthesiology; Anesthesiology